Mediating Tradition: The Role of Law Enforcement in Customary Law Disputes - Mansur, Teuku Muttaqin; Muazzin, Muazzin; Abdullah, M Adli; Ali, Hasbi; Usman, Musliadi Bin; Miranti, Aufa (SCAD Independent, 2025)
This study explores the role of law enforcement agencies in resolving customary law disputes in Bener Meriah and Nagan Raya Regencies, focusing on the integration of customary law with national law. The study addresses the challenges faced and the collaborations between law enforcement and customary leaders in settling disputes, particularly conflicts between customary and formal legal principles. Using a qualitative approach and case study methodology, data were gathered through in-depth interviews with key stakeholders, including police representatives, the Aceh Customary Council, and prosecutors, along with direct observations and a literature review. The findings indicate that while customary law is officially recognized within Aceh’s legal framework, significant challenges arise in harmonizing it with national law, especially in cases where their principles diverge. Law enforcement agencies, including the police and prosecutors, play a pivotal role in bridging these gaps by working with customary leaders to mediate disputes. These partnerships uphold local wisdom while ensuring compliance with formal legal standards. Case studies from both regencies demonstrate that dispute resolutions often seek a balance between maintaining customary values and adhering to national law. This study contributes to understanding how law enforcement can facilitate effective conflict resolution within a pluralistic legal system.